2013
DOI: 10.1093/nar/gkt575
|View full text |Cite
|
Sign up to set email alerts
|

Lighting up left-handed Z-DNA: photoluminescent carbon dots induce DNA B to Z transition and perform DNA logic operations

Abstract: Left-handed Z-DNA has been identified as a transient structure occurred during transcription. DNA B-Z transition has attracted much attention because of not only Z-DNA biological importance but also their relation to disease and DNA nanotechnology. Recently, photoluminescent carbon dots, especially highly luminescent nitrogen-doped carbon dots, have attracted much attention on their applications to bioimaging and gene/drug delivery because of carbon dots with low toxicity, highly stable photoluminescence and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 63 publications
3
67
0
Order By: Relevance
“…Photoluminescent carbon dots (CDs), with a diameter less than 10 nm, are considerably attractive for bioimaging and biosensor applications owing to their stable photoluminescence, broad excitation spectrum, tunable emission wavelength, excellent biocompatibility, and abundant functional groups on their surface . Recently, our group found that CDs can induce B‐DNA to Z‐DNA under physiological salt conditions with sequence and conformation selectivity . Compared to canonical right‐handed B‐DNA, Z‐DNA presents the left‐handed double helix and its phosphate backbone has a zigzag pattern.…”
Section: Logic Gates Based On Functional Materials and Nucleic Acidsmentioning
confidence: 99%
“…Photoluminescent carbon dots (CDs), with a diameter less than 10 nm, are considerably attractive for bioimaging and biosensor applications owing to their stable photoluminescence, broad excitation spectrum, tunable emission wavelength, excellent biocompatibility, and abundant functional groups on their surface . Recently, our group found that CDs can induce B‐DNA to Z‐DNA under physiological salt conditions with sequence and conformation selectivity . Compared to canonical right‐handed B‐DNA, Z‐DNA presents the left‐handed double helix and its phosphate backbone has a zigzag pattern.…”
Section: Logic Gates Based On Functional Materials and Nucleic Acidsmentioning
confidence: 99%
“…Transient Z‐DNA plays an important role in cell processes including transcription, chromatin recombination, and nucleosome positioning . Some molecules have been reported that can induce a B–Z DNA conformational transfer . For example, in the presence of a low concentration of [Co(NH 3 ) 6 ] 3+ , B‐DNA conformationally transforms into Z‐DNA .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Somem olecules have been reported that can induce aB-Z DNA conformational transfer. [9][10][11][12][13][14][15][16][17][18] For example, in the presence of al ow concentration of [Co(NH 3 ) 6 ] 3 + ,B-DNA conformationally transforms into Z-DNA. [11] More interestingly,w ith an increasing concentration of [Co(NH 3 ) 6 ] 3 + ,D NA turns into ah igh-orderc ompacts tructure.…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available poly(dI-dC)s were used as templates, and Klenow fragments were used to incorporate 8-oxo-2′-deoxyguanosine-5′-triphosphate into the synthetic polymers. 17 We next used the hexamer of 5′-CGCGCG-3′ with substituted 8-oxodG sites for study. To be different from polyCG, a typical Z-DNA conformation could be characterized on the CD spectrum of polyC-oxoG, 17 showing a positive band around 250 nm, an evident positive one around 270 nm and a dominant-negative one around 290 nm in the absence of NaCl (Fig.…”
mentioning
confidence: 99%